2020
DOI: 10.20896/saci.v8i2.742
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Services of Chariganga and Arpara Beel in Nadia District, West Bengal: A Geographical Enquiry

Abstract: The ecological set up of the deltaic Bengal has immensely been benefitted by the ecosystem services extended by the freshwater wetlands. Along with the diverse ecological benefits, those floodplain wetlands serve the adjacent agrarian community through the provision of free goods and services. The present study has attempted to identify the ecological resources provided by the Chariganga and Arpara Beel and its impact on the livelihood patterns of the rural inhabitants. Both qualitative and quantitative techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Focus group discussions and field surveys unveil that these wetlands provide an array of ecosystem services, from provisioning material resources to intangible cultural services, which put a significant impact on the economic and cultural livelihood patterns of the local people. Mandal et al (2020) have identified 33 ecosystem services (encompassing eight provisioning, 10 regulating, five cultural, and 11 supportive services), extended by these selected wetlands. The local people interact with the wetlands in 13 ways to collect the benefits of the ecosystem services.…”
Section: Discussionmentioning
confidence: 99%
“…Focus group discussions and field surveys unveil that these wetlands provide an array of ecosystem services, from provisioning material resources to intangible cultural services, which put a significant impact on the economic and cultural livelihood patterns of the local people. Mandal et al (2020) have identified 33 ecosystem services (encompassing eight provisioning, 10 regulating, five cultural, and 11 supportive services), extended by these selected wetlands. The local people interact with the wetlands in 13 ways to collect the benefits of the ecosystem services.…”
Section: Discussionmentioning
confidence: 99%
“…(Kumar et al, 2017;Kumari et al, 2020). Wetlands play an essential role in maintaining water quality and act as kidneys of the natural world (Mandal et al, 2020). Mizoram obtains sufficient wetlands in the forms of lakes/ponds, waterlogged, rivers/streams, reservoirs/barrages, and small wetlands (Table 3).…”
Section: Wetlandsmentioning
confidence: 99%